2014
DOI: 10.1007/s11031-014-9444-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of basic need satisfaction, motivational climate and personality to well-being and stress patterns among elite athletes: An explorative study

Abstract: PostprintThis is the accepted version of a paper published in Motivation and Emotion. This paper has been peerreviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the original published paper (version of record):Lundqvist, C., Raglin, J. (2015) The relationship of basic need satisfaction, motivational climate and personality to well-being and stress patterns among elite athletes: An explorative study. Correspondence concerning this article should be addressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…Tables 1 , 2 , 3 , 4 , 5 , 6 , 7 provide a summary of the key characteristics and main outcomes of the 60 included studies. For the purposes of reporting and analysis, studies were grouped according to the following major mental health constructs: anger and aggression ( N = 2) [ 29 , 30 ], anxiety ( N = 4) [ 31 34 ], eating disorder and body image ( N = 10) [ 21 , 35 43 ], general-prevalence studies ( N = 10) [ 23 , 44 52 ], help seeking ( N = 1) [ 11 ], sleep ( N = 1) [ 53 ], stress and coping ( N = 22) [ 64 86 ], substance use ( N = 9) [ 54 – 62 ] and wellbeing ( N = 1) [ 63 ]. The included studies examined athletes from a broad range of individual sports (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Tables 1 , 2 , 3 , 4 , 5 , 6 , 7 provide a summary of the key characteristics and main outcomes of the 60 included studies. For the purposes of reporting and analysis, studies were grouped according to the following major mental health constructs: anger and aggression ( N = 2) [ 29 , 30 ], anxiety ( N = 4) [ 31 34 ], eating disorder and body image ( N = 10) [ 21 , 35 43 ], general-prevalence studies ( N = 10) [ 23 , 44 52 ], help seeking ( N = 1) [ 11 ], sleep ( N = 1) [ 53 ], stress and coping ( N = 22) [ 64 86 ], substance use ( N = 9) [ 54 – 62 ] and wellbeing ( N = 1) [ 63 ]. The included studies examined athletes from a broad range of individual sports (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The 16 remaining studies (see Table 8 for a brief methodological summary, and Supplementary Table 7 for full details) investigated some aspect of motivation in relation to stress/distress and wellbeing (Lundqvist & Raglin, 2014;Pensgaard & Roberts, 2000), self-handicapping (Kuczka & Treasure, 2005), an intervention (Cook & Crewther, 2012;Mellalieu et al, 2009), antisocial/prosocial behaviour (Hodge & Gucciardi, 2015), narcissism (Roberts, Woodman, Lofthouse, & Williams, 2015), music (Laukka & Quick, 2013), hormonal concentrations (Cook et al, 2013), exercise dependence (Hamer & Vlachopoulos, 2002), coping (Ntoumanis, Biddle, & Haddock, 1999), gambling (Curry & Jiobu, 1995), and social behaviour (Hodge & Gucciardi, 2015). Furthermore, three studies examined the motivation of coaches (Alcaraz, Viladrich, Torregrosa, Ramis, & Gillham, 2015;Leidl, 2009;McLean & Mallett, 2012).…”
Section: Othermentioning
confidence: 99%
“…Several studies in different domains of life have confirmed the theoretical assumption that the satisfaction of basic psychological needs (e.g., through environments that support those needs) has positive consequences. Basic need satisfaction, for example, leads to emotional well-being ( Parfitt et al, 2000 ; Edmunds et al, 2007 ; Aldrup et al, 2017 ) and motivation ( Wilson et al, 2007 ; Devloo et al, 2015 ) in sports (further examples of the application of basic need theory in sports: Mullan et al, 1997 ; Pelletier and Sarrazin, 2007 ; Vallerand, 2007 ; Lundqvist and Raglin, 2015 ; see Hagger and Chatzisarantis, 2007 , for a summary).…”
Section: Introductionmentioning
confidence: 99%